Droplet Manipulation: Multifunctional Magnetocontrollable Superwettable‐Microcilia Surface for Directional Droplet Manipulation (Adv. Sci. 17/2019). Issue 17 (4th September 2019) - Ben, Shuang; Zhou, Tiantian; Ma, Han; Yao, Jinjia; Ning, Yuzhen; Tian, Dongliang; Liu, Kesong; Jiang, Lei
Abstract : Inspired by microorganisms' motile cilia, "self‐cleaning" lotus leaves, underwater superoleophobicity of filefish skin, and pigeons' migration behaviors, multifunctional, and magnetocontrollable superwettable‐microcilia surface devices to manipulate droplets are engineered and fabricated in article number1900834 by Kesong Liu and co‐workers. Droplets can be continuously transported in a specified direction via a superwettable‐microcilia array surface whose structure can be switched between different states via an external magnetic field.